2015
DOI: 10.1007/s00464-015-4490-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of delta-shaped intracorporeal double-tract reconstruction in totally laparoscopic proximal gastrectomy

Abstract: Totally laparoscopic delta-shaped intracorporeal double-tract reconstruction is a safe, feasible and minimally invasive reconstruction method with excellent postoperative outcomes in terms of preventing reflux esophagitis and anastomotic stenosis. TLPG-DT might serve as a promising treatment for proximal gastric cancer of early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
(32 reference statements)
2
17
0
1
Order By: Relevance
“…This enables food to enter the residual stomach more easily, because the bent distal jejunum reduces the outflow of the contents. Hong et al [30] reported a delta-shaped intracorporeal jejunogastrostomy in DTR in a procedure similar to ours. However, it was difficult to narrow the exit routes of the jejunum by twisting only the remnant stomach.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This enables food to enter the residual stomach more easily, because the bent distal jejunum reduces the outflow of the contents. Hong et al [30] reported a delta-shaped intracorporeal jejunogastrostomy in DTR in a procedure similar to ours. However, it was difficult to narrow the exit routes of the jejunum by twisting only the remnant stomach.…”
Section: Discussionsupporting
confidence: 76%
“…They suggested that the small amount of bile reflux to the interposed jejunum and tension to the interposed jejunum cause stenosis. In four studies [17,[29][30][31] of laparoscopic proximal gastrectomy with DTR, three reported postoperative complications. In the literature, there were no anastomosis-related complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Double-tract reconstruction after laparoscopic proximal gastrectomy using intracorporeal delta-shaped anastomosis has been also described by Jun Hong et al. [10] and shown to be technically feasible and safe. The length of the alimentary limb between esophagojejunostomy to gastrojejunostomy has been recommended to be 15–20 cm to achieve a satisfactory gastroendoscopic follow-up of the duodenum.…”
Section: Discussionmentioning
confidence: 89%
“…Pozostałe metody rekonstrukcji nie różnią się zasadniczo pod względem odsetka powikłań chirurgicznych, wyników odległych, oceny endoskopowej czy jakości życia, ale zalecane są prospektywne, wieloośrodkowe badania. Według najnowszych doniesień autorów azjatyckich resekcja proksymalna żołądka metodą DTR daje szereg korzyści metabolicznych, mniejszy odsetek refluksowego zapalenia przełyku, biegunki, anemii czy spadku masy ciała, a wyniki odległe (przeżycia całkowite, przeżycia wolne od choroby) nie różnią się w porównaniu z resekcją całkowitą metodą Roux-en-Y [5][6][7]. Rozpoczyna się właśnie koreańskie randomizowane, wieloośrodkowe badanie kliniczne dotyczące wyboru strategii postępowania chirurgicznego u chorych na wczesnego raka proksymalnej części żołądka [6].…”
Section: Omówienieunclassified